Co-creating group as a resource for customers’ value formation in a complex service : a case study on provider-driven joint building ventures - Laaksonen, Lauri (Vaasan yliopisto, 2021)
To enhance customer value formation, firms in increasingly complex industries are inviting customers to co-create offerings. This leads to services involving several actors simultaneously. A good example is a joint building venture (JBV), which has inspired this study. The complexity of this kind of group makes one question how to secure positive value formation for the customers. This study is theoretically mainly anchored in service marketing (SM) and especially in the customer dominant logic (CDL). Based on that, the assumption is that a customer acts guided by her logic and that value is formed from the experiences emerging out of her activities. Activities are in this study seen as resource integration. The purpose of this study is to generate understanding on how a co-creating group may become a resource for customers’ value formation in a complex service. Abductive case study methodology in a provider-driven JBV context is applied. The main data collection methods are narrative interviews with customers and observations of JBV-sessions. Customer logics identified from the data are utilized to illustrate the multifaceted resource potential of a co-creating group (RQ1). In addition, various critical conditions are found to influence the group becoming a resource for customer value formation (RQ2). These are e.g. the congruence between logics and roles and communication in accordance with customers’ desires. Persuasion and the use of social roles as resources in the customers’ relations as well as the customers’ understanding and the completion of the project with varying sources of value also emerge as focal conditions. The generated 12 propositions provide novel and elaborated understanding to the theory building on customer value formation in SM and especially the CDL. Focal contributions are the deepened understanding on customer logics and their relation to value formation as well as the enriched understanding on value co-creation. The managerial implications relate to the enhancement of customer value formation generally and in the co-creation of offerings. The ideas for future research concern customer logics and co-creation.

Edistääkseen asiakasarvonmuodostumista, yritykset entistä kompleksisimmilla toimialoilla kutsuvat asiakkaita mukaan tarjoaman yhteisluomiseen. Tämän myötä syntyy palveluita, joissa mukana on samanaikaisesti useita toimijoita. Hyvä esimerkki tästä on ryhmärakennuttaminen (RR), joka on inspiroinut tätä tutkimusta. Tällaisen ryhmän kompleksisuus saa kysymään, miten asiakkaille voidaan varmistaa positiivinen arvonmuodostuminen? Teoreettisesti tutkimus tukeutuu pääosin palvelumarkkinointiin (PM) ja erityisesti asiakaskeskeiseen näkökulmaan (CDL), jonka perusteella oletetaan, että asiakas toimii oman logiikkansa ohjaamana ja että arvo muodostuu aktiviteeteista syntyvistä kokemuksista. Aktiviteetit nähdään tutkimuksessa resurssien integroimisena. Tutkimuksen tarkoituksena on luoda ymmärrystä siitä, miten yhteisluovasta ryhmästä voi tulla resurssi asiakkaiden arvonmuodostumisessa monimutkaisessa palvelussa. Työssä käytetään abduktiivista tapaustutkimusmetodologiaa yritysvetoisessa RR-kontekstissa. Aineistonkeruumenetelmät ovat asiakkaiden narratiivihaastattelut sekä RR-tilaisuuksien havainnoinnit. Tulosten pohjalta tunnistettujen asiakaslogiikkojen avulla osoitetaan yhteisluovan ryhmän monimuotoinen resurssipotentiaali asiakkaille (Tutkimuskysymys 1). Lisäksi tunnistetaan kriittisiä ehtoja, jotka vaikuttavat ryhmän muotoutumiseen resurssiksi asiakasarvonmuodostumisessa (Tutkimuskysymys 2). Näitä ovat mm. logiikkojen ja roolien yhteensopivuus sekä asiakkaalle sopiva kommunikaatio. Suostuttelu ja sosiaalisten roolien käyttö resursseina asiakkaiden välisissä suhteissa sekä asiakkaiden relevantti ymmärrys ja projektin loppuunsaattaminen eri arvonlähteineen ilmenevät myös tärkeinä ehtoina. Tuotetut 12 propositiota luovat uutta ja jäsentynyttä ymmärrystä PM:n ja erityisesti CDL:n asiakasarvonmuodostukseen liittyvään teoriankehitykseen. Keskeisinä kontribuutioina ovat syvällisempi ymmärrys asiakaslogiikoista ja niiden suhteesta arvonmuodostumiseen sekä rikastettu ymmärrys arvon yhteisluomisesta. Liikkeenjohdolliset implikaatiot liittyvät asiakasarvonmuodostumisen edistämiseen yleisemmin ja tarjoaman yhteisluomisessa. Ideat jatkotutkimusaiheiksi kiinnittyvät asiakaslogiikkoihin ja yhteisluomiseen.
Yhteisluova ryhmä resurssina asiakkaiden arvonmuodostumisessa monimutkaisessa palvelussa : tapaustutkimus konsulttivetoisesta ryhmärakennuttamisesta
Keywords: co-creation; co-creating group; customer centricity; customer-dominant logic; customer logic; customer resources; customer value formation; value co-creation; customers; role related to value; services marketing; marketing; value creation; fi=Markkinointi|en=Marketing|